KINERJA CAMPURAN BERASPAL POROUS YANG MENGGUNAKAN AGREGAT LOKAL DARI BANTEN - Rindu Twidi Bethary; Dwi Esti Intari; Leo Affan Dzunnurain (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
Porous asphalt is a mixture of asphalt with low levels of fine aggregate with the aim of providing a large air cavity, so that high permeability can drain surface water into the soil but has low stability. One of the value effects of stability is the aggregate characteristics, where Banten province has quite a lot of aggregate availability, this is beneficial in reducing the cost of building and rehabilitating roads and overcoming the limitations of road construction materials. This study used a University of New Hampshire Stormwater Center (UNHSC) gradation with three types of porous asphalt mixtures with local aggregates, namely Lebak, Serang, and Merak with variations in asphalt content of 4.5%, 5.0%, 5.5%, 6, 0%, and 6.5%. Based on the results of testing the characteristics of the porous asphalt mixture material which includes aggregate, filler and asphalt meet the specifications of Bina Marga 2018, then from the Marshall test, the Optimal Asphalt Content was obtained by 5.5% for the three types of porous asphalt mixtures where all parameters meet the AAPA requirements. While the highest stability parameters were porous asphalt mixtures using Merak aggregate with low permeability coefficient values for the three porous asphalt mixtures. Keywords: porous asphalt, local aggregate, Asphalt Content, marshall, permeability.